Macroprudential regulation and bank stability: The credit market signal - Samuel Kiemo; Anne Kamau; Irene W. Rugiri; Camilla Talam (Kenya Bankers Association (KBA), 2021)
This paper examines the effectiveness of macroprudential regulations in promoting bank stability and credit in the Kenyan financial system. The study uses bank-level and nonbank credit data for the period 2001-2019 and applies a panel estimation methodology to achieve its objectives. The study finds that bank stability has remained high, though downward trending. The findings also reveal that capital-based and asset-side macroprudential regulations effectively promote bank stability, while the liquidity-related macroprudential regulation is ineffective. Additionally, there is evidence of dampened bank credit market and domestic leakage associated with macroprudential regulations. The paper cautions policymakers to implement macroprudential policies that balance the objectives of bank stability and credit conditions. Furthermore, policymakers should note that implementing the new macroprudential measures may cause financial intermediaries to adjust their behaviour and therefore, should be implemented systematically while observing their impact at each stage.
Keywords: E44; E51; G21; 330; Macroprudential Regulation; Stability; Lending; Banks